Pendidikan Literasi Kesehatan Lingkungan Bagi Anak Usia Dini - Saepudin, Encang; Damayani, Ninis Agustini; Rusmana, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
Efforts to change individual behavior and attitudes cannot be done separately, but rather involve various parties in the process. One effective approach is to integrate learning with the environment. This integration can be done in two ways, namely taking the class outdoors so that students interact directly with nature, or conversely, presenting environmental elements into the classroom as a learning resource. This study aims to improve early childhood understanding and awareness of environmental health issues through an educational approach that is tailored to their developmental characteristics. The method used is action research, which is carried out in two cycles at an early childhood education institution. Each cycle consists of the planning stage, action implementation, observation, and reflection, in order to evaluate the effectiveness of the actions given and design improvements for the next cycle. Data collection instruments include observations of children's behavior during the learning process, documentation of activities, and interviews with educators and students. The results of the study showed that the integration of environmental health literacy in learning activities, such as playing while learning, exploring the surrounding environment, and simple discussions about healthy living habits, can significantly improve children's understanding. Children showed an increase in recognizing the importance of personal hygiene, waste management, and maintaining clean air and water. This finding emphasizes that early childhood education is an important foundation in fostering environmentally friendly behavior and healthy lifestyles in the future.